A Changing Perspective with Weed Management in Semi-arid Cropping Systems - Anerson, Randy L (Annals of Arid Zone, 2016)
No-till cropping systems are improving precipitation-use-efficiency, increasing land productivity, and restoring soil health in semi-arid regions of the world. However, weed resistance, rising costs, and concern about environmental impacts are stimulating questions about the extensive reliance on herbicides with no-till. Scientists and producers are seeking a broader perspective with weed management. One approach is disrupting weed population growth with cultural tactics, thus supplementing herbicides in controlling weeds. This paper describes a successful system based on this approach in the semi-arid steppe of the United States that controls weeds with 50% less inputs, reduces need for herbicides, and increases net returns for producers. Two key components of this approach are rotation design and no-till. Rotations complised of crops with different life cycles, such as cool-season and warm-season crops, suppress weed population growth. No-till improves crop growth by its favorable impact on water relations and weed management by its detrimental impact on weed seed survival in soil. In addition, cultural tactics improve crop competitiveness to reduce weed seed production. We encourage scientists in semi-arid regions to integrate weed management with design of crop rotations, and also to consider crop diversity in regards to other aspects of crop production. Key words: Crop diversity, no-till, rotation design, weed population management.